Constant high-level visual acuity during total laparoscopic hysterectomy using the OpClear® system - R. Evans; A. Taylor (Journal of Obstetrics and Gynaecology)
Background Operative vision can frequently be critically reduced during laparoscopic surgery by condensation and other matter accumulating on the distal laparoscope lens. By delivering saline and carbon dioxide across the lens, the OpClear system is designed to maintain operative vision without needing scope removal for lens cleaning. This study evaluates the system’s efficacy in providing high-level visual acuity during laparoscopic hysterectomy while examining its utility through its impact on operative duration.Methods A retrospective audit compared efficacy and utility for the three years before and after the implementation of OpClear in a single unit. Thirty-three cases were reviewed pre-OpClear, while 82 cases were analysed in the post-OpClear group. All cases involved routine total laparoscopic hysterectomies (TLH) performed by the same surgeon (AT) with similar complexity levels.Results The OpClear system provided a consistently high level of visual acuity throughout the laparoscopic procedures. Scope removals, which typically result in non-productive operating time, were virtually eliminated. Consequently, in highly comparable cases, OpClear usage resulted in a 17-minute reduction in operating time over cases performed without the device. Additionally, in the OpClear group, there were trends towards reduced blood loss and shorter hospital stays, with patients in the OpClear group being discharged on first rather than second postoperatively.Conclusions The findings of this audit suggest that the OpClear system provides continuous high-level vision during laparoscopic hysterectomy. Further, reducing periods of non-productive time associated with scope removal for cleaning resulted in shorter operating times. Thus, the system has the potential to enhance safety, improve theatre utilisation and alleviate some of the surgical stresses associated with laparoscopic surgery.